Global context and regional imperatives of telecommunications in the states of CARICOM. - ALLEYNE, Mark D. (1994)
Sketches the history of telecommunications development in the region, and puts recent privatizations and expansions of the telecommunication sector in a global context. Discusses regional imperatives guiding, or that should guide, the planning of telecommunications.